Association of genetic variants, protein domains, and phenotypes in the ZMIZ1 syndromic neurodevelopmental disorder - Cormier, Kendall E.; Kantor, Belle L.; K C, Rajan; Blanco-Fernandez, Xabier; Galazo, Maria J. (Frontiers in Neuroscience, 2025)
BackgroundHuman genetic studies have linked loss-of-function variants in Zinc Finger MIZ-Type Containing 1 (ZMIZ1) to a spectrum of neurodevelopmental disorders (NDDs), such as intellectual disability (ID), autism spectrum disorders (ASD), and attention-deficit/hyperactivity disorder (ADHD). Recently, multiple studies have reported ZMIZ1 variants in patients with NDDs, in some cases providing detailed phenotypic descriptions of the carriers. However, how ZMIZ1 variants may contribute to the phenotypic variability of carriers and the different phenotypic manifestations of NDDs has not been explored.MethodsHere, we examine the relationship between ZMIZ1 variants, affected ZMIZ1 protein domains, and phenotypic variability of individuals diagnosed with NDD using de-identified data from 15 publicly available studies describing mutations in ZMIZ1. This study includes descriptions of ZMIZ1 disease-associated variants of 36 individuals diagnosed with NDDs: 35 single-nucleotide variants (SNVs) and 1 deletion, all in the coding sequence. Pathogenicity scores and records for these variants were obtained from AlphaMissense, PolyPhen, and ClinVar and were correlated to the variants’ locations across protein domains. Phenotypic descriptions were obtained from publicly available reports. To further explore the potential functional impact of SNV on ZMIZ1, protein folding predictions of wild-type and mutated ZMIZ1 were performed using AlphaFold.ResultsWe find that patients with SNVs in the Alanine-rich domain show strong association with diagnosis of ID (62.5%), motor delay (70%), and other physical phenotypic manifestations (100%), while ASD diagnosis in combination with ID is more strongly associated with mutations in TPR and Proline-rich domains. Morphological alterations in the brain and cranium are highly prevalent in individuals with missense mutations in ZMIZ1, without any association to specific protein domains. Missense mutations in the Alanine-rich and TPR domains are predicted to alter the relative position of domains and ZMIZ1 3D configuration.ConclusionOverall, our study highlights the impact of mutations across ZMIZ1 domains and their association with distinct neurodevelopmental phenotypes in individuals with ZMIZ1 variants, which will lead to better interpretation of ZMIZ1 variants and diagnosis of patients with ZMIZ1 neurodevelopmental syndrome.